1999
DOI: 10.1128/aem.65.12.5484-5492.1999
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of Free Phytol by Bacterial Communities Isolated from Marine Sediments under Aerobic and Denitrifying Conditions

Abstract: Biodegradation of (E)-phytol [3,7,11,15-tetramethylhexadec-2(E)-en-1-ol] by two bacterial communities isolated from recent marine sediments under aerobic and denitrifying conditions was studied at 20°C. This isoprenoid alcohol is metabolized efficiently by these two bacterial communities via 6,10,14-trimethylpentadecan-2-one and (E)-phytenic acid. The first step in both aerobic and anaerobic bacterial degradation of (E)-phytol involves the transient production of (E)-phytenal, which in turn can be abiotically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(22 citation statements)
references
References 47 publications
0
22
0
Order By: Relevance
“…This implies that NAs belonging to the Z ¼ )4 family are not degraded via b-oxidation, because b-oxidation is a widely available catabolic pathway under aerobic and anaerobic conditions. For example Rontani et al (1999) found that two different bacterial communities isolated from marine sediments under aerobic and denitrifying conditions were able to completely mineralize (E)-phytol (3,7,11,15-tetramethylhexadec-2(E)-en-1-ol) and that in both cases the mineralization occurred by alternating b-decarboxymethylation and b-oxidation. A possible mechanism for the aerobic biodegradation of bicyclic NA is the b-oxidation of the carboxylated side-chain followed by a decarboxylation reaction to give the bicyclic hydrocarbon, which in turn can be hydroxylated followed by an oxidation reaction to give the corresponding cyclic ketone.…”
Section: Discussionmentioning
confidence: 99%
“…This implies that NAs belonging to the Z ¼ )4 family are not degraded via b-oxidation, because b-oxidation is a widely available catabolic pathway under aerobic and anaerobic conditions. For example Rontani et al (1999) found that two different bacterial communities isolated from marine sediments under aerobic and denitrifying conditions were able to completely mineralize (E)-phytol (3,7,11,15-tetramethylhexadec-2(E)-en-1-ol) and that in both cases the mineralization occurred by alternating b-decarboxymethylation and b-oxidation. A possible mechanism for the aerobic biodegradation of bicyclic NA is the b-oxidation of the carboxylated side-chain followed by a decarboxylation reaction to give the bicyclic hydrocarbon, which in turn can be hydroxylated followed by an oxidation reaction to give the corresponding cyclic ketone.…”
Section: Discussionmentioning
confidence: 99%
“…, C24:1-CoA were enzymatically synthesized from the corresponding saturated CoA esters using acyl-CoA oxidase from Arthrobacter (Sigma-Aldrich). A mixture of cis-and trans-phytenic acid was synthesized as described previously [9]. A mixture of cis-and trans-phytenoyl-CoA isomers was chemically synthesized from this mixture as described before [10].…”
Section: Methodsmentioning
confidence: 99%
“…The phytanic acid-rich particles would be available in the water column for consumption by bacteria possessing the α-oxidation pathway Additionally, it is possible that phytol may accumulate in particles that sink into the anoxic hypolimnion of lakes. Since the α-oxidation pathway requires oxygen (through the essential phytanoyl CoA hydroxylase), phytol may accumulate under anoxic conditions, although anaerobic degradation of phytol in sediments has been reported (Rontani et al, 1999). Nevertheless, during breakdown of stratification in autumn, phytol accumulated in the hypolimnion could serve as a carbon reserve supporting microbial metabolism throughout the winter.…”
Section: Scavenging Of the Phytol Moiety Of Chlorophyllmentioning
confidence: 99%